The Study of Bureaucracy in the Administrative Organizations of Iran (The Case of Personnel of Govermental Organizations in Ahwaz City) - Allameh, Sajedeh; Hosseinzade, A. H. (Advances in Social Sciences Research Journal, 2018)
This study represents an attempt to examine bureaucracy in the administrative organizations of Iran as a developing country. Therefore, this study aims to study how the bureaucratic structure of organization and its dimensions are in the administrative organizations of Iran. This study was carried out through the survey method. The data research have been collected by survey from a sample 400 person taken from the staffs population of 30 governmental organizations of Ahwaz through stratified cluster sampling. The results showed that bureaucracy in the administrative organizations of Iran is multidimensional and it can’t be considered as an unitary concept. Also, six dimensions of bureaucratic structure form two high-order factors that are inversely correlated together. First factor is control including Hierarchy of authority, rule observation and formality in relations(impersonality). Second factor is expertise including job codification, technical competence and division of labor. Also, it was seen differences between western bureaucratic models and bureaucracy in the administrative organizations of Iran as a developing country.